Autoantibodies to neuronal antigens in children with focal epilepsy and no prima facie signs of encephalitis. (July 2016) - Borusiak, Peter; Bettendorf, Ulrich; Wiegand, Gert; Bast, Thomas; Kluger, Gerhard; Philippi, Heike; Münstermann, Dieter; Bien, Christian G.
Abstract: Objective: There is increasing awareness of neuronal autoantibodies and their impact on the pathogenesis of epilepsy. We investigated children with focal epilepsy in order to provide an estimate of autoantibody frequency within a pediatric population without prima facie evidence of encephalitis using a broad panel of autoantibodies. This was done to assess the specificity of antibodies and to see whether antibodies might be of modifying influence on the course of focal epilepsies. Method: We searched for autoantibodies in 124 patients with focal epilepsy (1–18 years; mean 10; 6 years). Sera were tested using a broad panel of surface and intracellular antigens. Results: We found autoantibodies in 5/124 patients (4%): high-positive GAD65 antibodies ( n = 1), low-positive GAD65 antibodies ( N = 1), VGKC complex antibodies not reactive with LGI1 or CASPR2 ( n = 3). We did not find any distinctive features distinguishing antibody positive patients from those without antibodies. Conclusions: The antibodies found in this cohort are probably neither disease-specific nor pathogenic. This has been suggested before for these antigenic targets. Moreover, they do not seem to modify disease severity in the antibody-positive epilepsy patients. Highlights: 5/124 children with focal epilepsy without evidence for encephalitis had autoantibodies. We did not find any distinctive features distinguishing antibody positive patients. Antibodies in these children are not syndrome specific and probably not pathogenic. Antibodies may in some cases be biomarkers for inflammatory processes in a broad sense.